1994
DOI: 10.1073/pnas.91.17.8122
|View full text |Cite
|
Sign up to set email alerts
|

A functional anatomical study of associative learning in humans.

Abstract: The purpose of the study was to map the functional neuroanatomy of simple associative learning in humans. Eyeblink conditioning was studied in eight normal volunteers using positron emission tomography and H2150.Regional cerebral blood flow was assessed during three sequential phases: (i) explicitly unpaired presentations of the unconditioned stimulus (air puff to the right eye) and conditioned stimulus (binaural tone), (ii) paired presentations of the two stimuli (associative learning), and (Wi) presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
161
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(188 citation statements)
references
References 37 publications
26
161
1
Order By: Relevance
“…Miller et al (2003) found an acquisition-related fMRI signal decrease in bilateral lobule VI in rabbits. Previous positron emission tomography (PET) studies in humans showed both increases of regional cerebral blood flow (rCBF; Blaxton et al, 1996;Parker et al, 2012) and glucose metabolism (Logan and Grafton, 1995), as well as decreases of rCBF (Molchan et al, 1994;Schreurs et al, 1997Schreurs et al, , 2001Parker et al, 2012). Based on the present findings the assessment time during the course of learning is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al (2003) found an acquisition-related fMRI signal decrease in bilateral lobule VI in rabbits. Previous positron emission tomography (PET) studies in humans showed both increases of regional cerebral blood flow (rCBF; Blaxton et al, 1996;Parker et al, 2012) and glucose metabolism (Logan and Grafton, 1995), as well as decreases of rCBF (Molchan et al, 1994;Schreurs et al, 1997Schreurs et al, , 2001Parker et al, 2012). Based on the present findings the assessment time during the course of learning is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…PET studies suggest that partly overlapping areas in the cerebellar cortex support acquisition and extinction in humans (Schreurs et al, 1997(Schreurs et al, , 2001Parker et al, 2012). Our findings agree with these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Most-extensively studied in the primary auditory cortex, associative representational plasticity has been reported for cortical metabolism (Gonzalez-Lima & Scheich, 1986a), receptive field properties (Bakin & Weinberger, 1990;Blake, Strata, Churchland, & Merzenich, 2002;Edeline, Neuenschwander-el Massioui, & Dutrieux, 1990;Gao & Suga, 2000) and tonotopic maps (Rutkowski & Weinberger, 2005) in animals, as well as in studies of human brain imaging (Molchan, Sunderland, McIntosh, Herscovitch, & Schreurs, 1994;Morris, Friston, & Dolan, 1998;reviewed in Weinberger 1995reviewed in Weinberger , 2004aPalmer, Nelson, & Lindley, 1998;Rauschecker, 2003;Buonomano & Merzenich, 1998). Learning-related plasticity in A1 develops in a wide range of tasks, including habituation (Condon &Weinberger, 1991), classical reward (Kisley & Gerstein, 2001) and aversive (Bakin & Weinberger, 1990) conditioning, instrumental reward (Blake et al, 2002) and avoidance (Bakin, South, & Weinberger, 1996) learning, category learning (Ohl, Scheich, & Freeman, 2001), long-term training in perceptual discrimination learning (Recanzone, Schreiner, & Merzenich, 1993), working memory (Brechmann et al, 2007;Sakurai, 1994), reference memory (Sakurai, 1994) and motor planning (Villa, Tetko, Hyland, & Najem, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most research on auditory plasticity involved rodents, cats, or nonhuman primates, but some related evidence comes from human neuroimaging studies, with PET (8,9) or functional (f) MRI (10). Here, we used magnetoencephalography (MEG) (11,12) to address human auditory plasticity in an aversive classicalconditioning paradigm (1)(2)(3), focusing on the well-known, successive, auditory-evoked field components P1m, N1m, and P2m (13,14).…”
mentioning
confidence: 99%